Goddess regarded as an incarnation of Parvati - Mumbai Archive Project Team (Jio Institute, 2024)
Goddess Gauri is regarded as an incarnation of Parvati, Lord Shiva’s consort and mother of Lord Ganesha. She is honoured as the Goddess of fertility, marital bliss, and prosperity. For the Koli community, Gauri is the protector of their homes and livelihoods, blessing them with bountiful catches and harmonious lives.